Analysis of the Current Research Status and Optimization Paths of Health Resource Allocation in China - Yun Lu; Qiang He (Scientific Journal Of Humanities and Social Sciences, 2026)
Objective To systematically review the prominent problems existing in the field of health resource allocation in China, so as to provide a reference for optimizing resource layout. Methods The literature research method was adopted to summarize and analyze relevant studies from four dimensions: spatial layout, operational efficiency, talent team, and external environment. Results There are problems in health resource allocation in China, such as imbalanced spatial layout, low operational efficiency, structural shortage of the talent team, and insufficient dynamic adaptability. Conclusion It is necessary to establish a dual-dimension allocation standard based on population and geography, improve regional coordination and counterpart assistance mechanisms, promote the transformation towards efficiency improvement and technology-driven development, take multiple measures to strengthen talent team construction, and enhance the dynamic adaptability to changes in the external environment.